Angiographers no longer need to avoid digital zoom. Issue 1 (20th July 2018) - Cecil, Robert A.; Heupler, Frederick; Shkumat, Nicholas; Ellis, Stephen; Kapadia, Samir; Fares, Haitham; Agarwal, Ashok
Abstract: The physics of angiographic digital flat‐panel detectors suggests that no increase in dose is required for appropriate image quality in image‐magnified fields of view. This is contrary to current practice. A dose‐saving protocol decreased radiation dose by an average of 32% for these zoomed fields of view with no observable image quality degradation. This change in protocol may be applicable across all manufactures of flat‐panel angiographic systems. Angiographers may preferentially use reduced‐dose zoomed fields to minimize scatter radiation, assure anatomical conspicuity and reduce patient radiation burden.